Corporate governance and the level of voluntary disclosure in Singapore listed companies. - Chia, Sook Leng. (2008)
This study deals with corporate governance mechanisms and the impact these mechanisms have on the level of voluntary disclosure in a sample of 150 singapore listed companies. Our results identified a number of corporate governance variables that are significantly related to the level of voluntary disclosure.